Job requirements and workers' learning: formal gaps, informal closure, systemic limits - Livingstone, David W. [Verfasser] (My University, 2010)
"There is substantial evidence that formal educational attainments increasingly exceed the educational job requirements of the employed labour force in many advanced market economies - a phenomenon variously termed 'underemployment', 'underutilisation', or 'overqualification'. Conversely, both experiential learning and workplace case studies suggest that workers continually negotiate such 'gaps'. This paper summarises results of recent national labour force surveys and workplace case studies in Canada to further assess the relations between workers and their jobs. Underemployment is found to be increasing among all types of employees. Underemployment is found to decline with work experience but persists in virtually all categories of employees - most notably service and industrial working classes and among non-white immigrant workers. Case studies of teachers, computer programmers, clerical workers, autoworkers and disabled workers demonstrate how underemployed workers as well as others engage in continual learning and try to reshape their jobs. Implications of these findings are identified in terms of the incompatibility of narrow economic market objectives with wider social objectives of democratic education, and of the systemic limits of appeals for still greater formal educational efforts by already highly educated and continually learning labour forces." (Autorenreferat, BIBB-Doku)
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; T 3 Forschungsmethoden; I 2.3.2 Nordamerika; Arbeitsanforderungen; Bildungsniveau; Berufserfahrung; Unterbeschäftigung; Arbeitnehmer; Erwerbstätiger; Fallstudie; Lehrer; Programmierer; Beamter; Fahrzeugbauer; Menschen mit Behinderung; Kanada